Pengangkatan Anak dan Akibat Hukumnya di Pengadilan Agama Jombang: (Analisis Penetapan Perkara Nomor 611 Pdt.P 2022 PA.Jbg.) - M. Al Amin Ilman Huda; Mashudi Mashudi (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2023)
Adoption is taking other people's children to be their own children. The process of adopting a child must go through a court order. This determination is made by the prospective adoptive parents and the biological parents of the child who is adopted to submit a case for the application for adoption to the Religious Courts. The government issued a policy for the welfare and protection of adopted children so that they have legal force by passing Law Number 3 of 2006 concerning Amendments to Law Number 7 of 1989 Article 49 letter (a) number (20) concerning the Religious Courts. This type of research is field research conducted at the Class IA Jombang Religious Court to obtain primary and secondary data. Primary data is used to obtain information about the judge's considerations in giving a determination of adoption and the court process for determining adoption. Obtained by interviewing Judges who have experience in determining cases of adoption. Secondary data is data related to this research in the form of copies of stipulations and books related to stipulations of child adoption. The results of this study are to discuss cases of stipulation of child adoption in the Jombang Religious Court in receiving, examining, adjudicating and deciding the case so that can generate determinations. The case discussed in this study is Case Number 611/Pdt.P/2022/PA.Jbg at the Jombang Religious Court, in this case the Panel of Judges granted and determined the case for determining the adoption of a child by the applicant by looking at various aspects and existing considerations. The Panel of Judges gave a stipulation in this case through considerations that support the granting of the request, these considerations are due to several reasons and facts that exist and deserve to be accepted and given a stipulation by the Panel of Judges on the basis of positive law and the basis of Islamic law which governs it, so that will strengthen the stipulation handed down by the Panel of Judges during the trial in giving the stipulation of child adoption to the applicant. In the trial for the determination of adoption there are no replic and duplic because in this case there is no dispute or opponent, so the stipulation is only stipulation (declaratoir). Therefore, the Government enacted Law Number 54 of 2007 concerning adoption which also plays a role in outreach to the community through activities: counseling, consultation, counselling, mentoring and training to help the community get information and understand the requirements, procedures and procedures method of adoption.